The Calcium-Sensing Receptor and the Parathyroid: Past, Present, Future - Conigrave, Arthur D. (Frontiers in Physiology, 2016)
Parathyroid hormone (PTH) defends the extracellular fluid from hypocalcemia and has powerful and well-documented actions on the skeleton and renal tubular system. To achieve a satisfactory stable plasma calcium level, the secretion of PTH, and the resulting serum PTH level, is titrated carefully to the prevailing plasma ionized Ca2+ concentration via a Ca2+ sensing mechanism that mediates feedback inhibition of PTH secretion. Herein, I consider the properties of the parathyroid Ca2+ sensing mechanism, the identity of the Ca2+ sensor, the intracellular biochemical mechanisms that it controls, the manner of its integration with other components of the PTH secretion control mechanism, and its modulation by other nutrients. Together the well established, recently elucidated, and yet-to-be discovered elements of the story constitute the past, present, and future of the parathyroid and its calcium-sensing receptor (CaSR).